Impact of the growth hormone and IGF-1 on graft function and immune response in pediatric liver recipients - R. M. Kurabekova; O. M. Tsirulnikova; S. Yu. Oleshkevich; I. E. Pashkova; G. A. Olefirenko (Вестник трансплантологии и искусственных органов)
Growth hormone (GH) and insulin-like growth factor 1 (IGF-1) are the most important regulators of growth, regeneration and metabolism. The influence of GH and IGF-1 on pediatric liver transplant outcomes is mediated through growth and body weight regulation, specific effects on hepatocyte function and immune system activity. In recent years, the blood levels of these factors and life expectancy, both in healthy individuals and liver recipients, have been shown to be correlated. In pediatric liver recipients, neurohumoral regulation of graft function and other functions of the growing organism, has not been studied enough. The results of studies on the levels and dynamics of GH and IGF-1 in the blood of liver recipients can serve as a basis for assessing the state of graft using new minimally invasive methods and identifying therapeutic targets for personalized therapy. This review summarizes the current understanding of the significance of GH/IGF-1 hormones in hepatobiliary diseases and pediatric liver transplantation (LTx).